2021
DOI: 10.1101/2021.03.25.21254330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the effectiveness of government interventions in Europe’s second wave of COVID-19

Abstract: As European governments face resurging waves of COVID-19, non-pharmaceutical interventions (NPIs) continue to be the primary tool for infection control. However, updated estimates of their relative effectiveness have been absent for Europe's second wave, largely due to a lack of collated data that considers the increased subnational variation and diversity of NPIs. We collect the largest dataset of NPI implementation dates in Europe, spanning 114 subnational areas in 7 countries, with a systematic categorisati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 46 publications
4
62
0
Order By: Relevance
“…In another preprint, Ge et al 99 analysed the effect of NPIs from the first wave until March 2021 in 133 countries, assessing vaccine rollouts as well. Consistent with Sharma et al 98 , Ge et al 99 observed differences in the effectiveness of NPIs during the different waves; they found that school closing was the most effective measure during the first wave, but not among the most relevant in the second. Gathering restrictions and facial covering requirements were consistently considered effective among waves, whereas international travel restrictions played a more important role in the control of the second wave.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In another preprint, Ge et al 99 analysed the effect of NPIs from the first wave until March 2021 in 133 countries, assessing vaccine rollouts as well. Consistent with Sharma et al 98 , Ge et al 99 observed differences in the effectiveness of NPIs during the different waves; they found that school closing was the most effective measure during the first wave, but not among the most relevant in the second. Gathering restrictions and facial covering requirements were consistently considered effective among waves, whereas international travel restrictions played a more important role in the control of the second wave.…”
Section: Discussionsupporting
confidence: 55%
“…However, several studies analysing the effectiveness of NPIs during the second wave have been released as preprints recently. Sharma et al 98 studied the implementation effects of 17 NPIs in 114 subnational areas from 7 European countries. They found that the combined effect of general NPI implementation was smaller during the second wave, which can be attributed, among other factors, to the influence of maintained individual protective behaviours after the first wave.…”
Section: Discussionmentioning
confidence: 99%
“…The Mask mandates are typically encoded as binary indicators that signal whether mask-wearing was required in at least some shared spaces [16,19,[29][30][31]. We draw mandate data from the OxCGRT NPI database [32].…”
Section: Resultsmentioning
confidence: 99%
“…Studying 41 countries, [18] infer an inconclusive mandate effect on COVID-19 transmission centred around zero. [19] is a regional study of 7 European countries [19] which finds an overall 7% to 17% (95% CI) reduction in transmission associated with mandates. In a mixed study of mask recommendations, mask mandates, cultural norms favouring masks, and self-reported wearing data, Leffler et al (2020) [16] find a 26% decrease in COVID-related mortality associated with their mixed proxy for mass mask-wearing.…”
Section: Effects Of Mass Mask-wearing Measured By Mandate Timingmentioning
confidence: 99%
See 1 more Smart Citation